87.1k views
5 votes
Need the correct answer please asap

Need the correct answer please asap-example-1

1 Answer

6 votes

Answer:

B. 288 In

Explanation:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

x*(x-2)-(288)=0

x • (x - 2) - 288 = 0

Find two factors of -288 whose sum equals the coefficient of the middle term, which is -2 .

-288 + 1 = -287

-144 + 2 = -142

-96 + 3 = -93

-72 + 4 = -68

-48 + 6 = -42

-36 + 8 = -28

-32 + 9 = -23

-24 + 12 = -12

-18 + 16 = -2 That's it

Answer: 288

User Gyurisc
by
6.4k points